Are the Experts Really Experts? a Cognitive Ergonomics Investigation for Project Estimations - Budi Hartono; Bhery Aditya Saputra (Jurnal Teknik Industri: Jurnal Keilmuan dan Aplikasi Teknik Industri, 2012)
Uniqueness is a major characteristic of any project systems. Hence it is virtually in-feasible for project analysts to utilize data from past projects as references for subsequent project planning and scheduling. Most project analysts would then depend on intuition, gut feeling and experiences to develop quantitative models for project scheduling and analysis which, according to past studies, is prone towards systematic errors. This study attempts to investigate the perfor-mance of both ‘experts’ and ‘non-experts’ when utilizing their cognitive capability to estimate pro-ject durations in group/non-group settings. A cognitive ergonomics perspective -which views human capability to make judgment as rationally bounded - is utilized in this investigation. An empirical approach is used to inquiry data from ‘projects’ on which ‘experts’ and ‘non-experts’ are required to provide prior estimate on project durations. The estimates are then gauged against the actual duration. Results show that some systematic cognitive judgmental errors (biases) are observable for both experts and non-experts. The identified biases include: anchoring bias as well as accuracy bias.